Tyrosine supplementation does not influence the capacity to perform prolonged exercise in a warm environment - Watson, P.; Maughan, R. J. (The biomedical basis of elite performance. 19-21 March 2012, London, UK. Abstracts & Manuscripts, 2012)
Since dopamine and noradrenaline are intrinsically involved in motivation, arousal, reward and motor control, it might be expected that strategies to increase catecholaminergic neurotransmission would enhance exercise performance. With local ethics committee approval, eight trained males (Mean ± SD age 23 ± 3 y; height 1.82 ± 0.06 m; body mass 80.0 ± 9.6 kg; VO2max: 5.2 ± 0.3 L/min) were recruited to examine the effect of acute supplementation with tyrosine (TYR), the amino acid precursor of the catecholamines, on the capacity to perform prolonged exercise in a warm environment. Subjects entered the laboratory in the morning and remained seated for 1 h, before cycling to volitional exhaustion at 70% VO2max in a warm environment (30.2 ± 0.2°C, 50 ± 1% rh). Two 250 mL aliquots of a placebo or a TYR solution were ingested at 30 min intervals prior to exercise, with an additional 150 mL consumed every 15 min throughout exercise (total TYR dose: 150 mg/kg body mass). A series of computer-based tests was completed prior to drink ingestion, at the end of the rest period and at exhaustion. TYR ingestion had no effect on exercise capacity (placebo 61.4 ± 13.7 min; TYR 60.2 ± 15.4 min; P = 0.505). No differences in heart rate (P = 0.380), core temperature (P = 0.554), weighted mean skin temperature (P = 0.167) or perceived exertion (P = 0.790) were apparent between trials. Ingestion of TYR caused an elevation in plasma TYR concentration immediately prior to exercise (+236 ± 46mmol/L; P < 0.001), resulting in a 5 ± 1-fold increase in the plasma concentration ratio of TYR to the remaining large neutral amino acids (P < 0.001). No change was apparent during the placebo trial (P = 0.924). Exercise caused an increase in error rate during the complex component of the Stroop test (P = 0.034), but there was no difference in the number of errors between trials at exhaustion (placebo 4 ± 1; TYR 4 ± 1; P = 0.106). No other aspect of cognitive function was altered by the protocol (all P > 0.05). Acute oral supplementation of 150 mg/kg BM TYR did not influence exercise capacity in the heat, measures of cognitive function, or the physiological response to exercise when compared to a placebo condition.